REDEFINING ESG DISCLOSURE THROUGH THE FRAMEWORK OF MAQASID SHARIAH: A STUDY ON PTPN - Widiyanti, Novi Wulandari; Sulistiyo, Agung Budi; Putri, Imamatin Listya; Fakhrurrozi, Muhammad Dhito (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to interpret Environmental, Social, and Governance (ESG) disclosures using the Maqasid al-Shariah framework. The selected research object is PT Perkebunan Nusantara (PTPN). PTPN is a state-owned enterprise with sustainability programs, such as Social and Environmental Responsibility (TJSL) and Corporate Social Responsibility (CSR), which are designed to empower communities, protect the environment, and support economic development. ESG disclosure in Indonesia is regulated by the Financial Services Authority (POJK 51/2017) and international sustainability standards such as GRI Standards. However, existing government regulations and international standards still have limitations in relating them to Islamic values, especially maqashid syariah. The gap in this research lies in the lack of integration of the sharia perspective in ESG literature, even though maqasid syariah offers a more holistic ethical, spiritual, and sustainability dimension. This study uses a qualitative approach with a case study design, where data is collected through document analysis (annual reports, sustainability reports, ESG policies) and semi-structured interviews with managers in the TJSL PTPN field. Data analysis was conducted using thematic analysis to map the alignment between ESG indicators and the principles of Sharia maqasid, namely hifz al-din (preserving religion), hifz al-nafs (soul), hifz al-'aql (mind), hifz al-nasl (progeny), and hifz al-mal (wealth). The results of this study are expected to broaden the understanding of ESG disclosure from an Islamic perspective, contribute theoretically to the development of shariah enterprise theory , and provide practical implications for the formulation of shariah-based sustainability reporting standards in Indonesia.